The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/radm.12305
|View full text |Cite
|
Sign up to set email alerts
|

Developing organizational agility in product innovation: the roles of IT capability, KM capability, and innovative climate

Abstract: This study investigates how to leverage information technology (IT) capability to build organizational agility in the context of product innovation. A moderated mediating model is proposed from the capability-building processes perspective. The data collected from 194 senior executives of firms in China show that knowledge management capability partially mediates the relationship between IT capability and organizational agility. Innovative climate also positively moderates the indirect relationship between IT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 107 publications
3
63
0
Order By: Relevance
“…Recently, the concept of agility has drawn significant attention of a wide-ranging IS researchers (Bi, Davison, Kam, & Smyrnios, 2012; Chakravarty, Grewal, & Sambamurthy, 2013; Galliers, 2007; Overby et al, 2006; Nazir & Pinsonneault, 2012; Tallon & Pinsonneault, 2011). The phrase ‘agile’ mostly defines organizations that are able to adjust and execute well in fast changing environments (Cai et al, 2013; Chen et al, 2015; Dove, 2001; Lu & Ramamurthy, 2011; Mao, Liu, & Zhang, 2015a, 2015b). Dynamic capabilities (Teece, Pisano, & Shuen, 1997), market orientation (Narver & Slater, 1990), strategic flexibility (Hitt, Keats, & Demarie, 1998) and absorptive capacity (Zahra & George, 2003), etc., are few critical concepts in the field of management on which the theory of agility may be built upon.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of agility has drawn significant attention of a wide-ranging IS researchers (Bi, Davison, Kam, & Smyrnios, 2012; Chakravarty, Grewal, & Sambamurthy, 2013; Galliers, 2007; Overby et al, 2006; Nazir & Pinsonneault, 2012; Tallon & Pinsonneault, 2011). The phrase ‘agile’ mostly defines organizations that are able to adjust and execute well in fast changing environments (Cai et al, 2013; Chen et al, 2015; Dove, 2001; Lu & Ramamurthy, 2011; Mao, Liu, & Zhang, 2015a, 2015b). Dynamic capabilities (Teece, Pisano, & Shuen, 1997), market orientation (Narver & Slater, 1990), strategic flexibility (Hitt, Keats, & Demarie, 1998) and absorptive capacity (Zahra & George, 2003), etc., are few critical concepts in the field of management on which the theory of agility may be built upon.…”
Section: Review Of Literaturementioning
confidence: 99%
“…From a business viewpoint, modules deal with groups of people, while from a technical angel it represents a collection of software components or machines. The responding component of agility is regarded as the ‘response ability’, which is the physical capability to act and the sensing component is concerned with the ‘knowledge management’, that represents the intellectual aptitude to identify suitable things to act on (Cai et al, 2013; Joshi, Farooquie, & Chawla, 2016; Liu, Song, & Cai, 2014; Mao et al, 2015a). The role of IT to support both the sensing and responding constituents of agility by spreading out the reach and richness of firm knowledge and processes is explained by the work conducted by Overby et al (2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The infrastructure for supporting the innovative development has been formed: special economic zones that provide significant benefits to innovative organizations, business incubators, technology parks, technology transfer centers, and prototyping centers etc. The following support forms for the innovative development of industrial enterprises can be identified (Cai, Liu, Huang, & Liang, 2019; Camison-Haba, Clemente-Almendros, & Gonzalez-Cruz, 2019): § Development of national development programs to support innovative enterprises; § Provision of benefits and preferences (including preferential taxation and tax deductions) that promote the interaction between industrial enterprises, research institutes and universities; § Direct lending (granting loans at reduced interest rates, interest-free lending, or free loans); § Direct financing (targeted grants and subsidies); § Creation of private innovation funds, venture funds; investment of budget funds in the capital of venture funds; § Using the public-private partnership system; § Implementation of the targeted public procurement of innovative products and services; § Financing of business incubators, technology parks, and other innovative infrastructure objects.…”
Section: Resultsmentioning
confidence: 99%
“…IT Alignment à Firm Performance Palmer and Markus (2000) not correlated Tallon and Pinsonneault (2011) not significantly negative Bergeron, Raymond, and Rivard (2004) significantly positive Chan, Sabherwal, and Thatcher (2006) significantly positive Cai, Liu, Huang, and Liang (2017) not significant Baum and Wally (2003) negatively affect These research gaps are the main reason for this study to provide the right solution by adding mediating variables in the relationship between alignment with company performance, where company performance in this study uses sustainable competitive advantage. Companies that do not have a competitive advantage will be unable to compete with other companies so that performance decreases.…”
Section: Researchermentioning
confidence: 92%